2016
DOI: 10.1200/jop.2015.010066
|View full text |Cite
|
Sign up to set email alerts
|

Easier Said Than Done: Keys to Successful Implementation of the Distress Assessment and Response Tool (DART) Program

Abstract: Key factors in the success of DART implementation were the adoption of a programmatic approach, strong institutional commitment, and a primary focus on clinic-based response. We have demonstrated that large-scale routine screening for distress in a cancer center is achievable and has the potential to enhance the cancer care experience for both patients and staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 51 publications
1
78
0
1
Order By: Relevance
“…18 The mechanism of pain in DT is complex and multifactorial, but clinical experience suggests it is often considered out of proportion to the physical effects of the DT, raising the possibility of emotional distress contributing to a presentation of total pain. 22 As benign DT and malignant sarcoma are both connective tissue diseases, they are seen at our institution within the same clinic and are treated by the same physicians and multidisciplinary approach. Thus, we formally investigated symptom distress in our patients with DT.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…18 The mechanism of pain in DT is complex and multifactorial, but clinical experience suggests it is often considered out of proportion to the physical effects of the DT, raising the possibility of emotional distress contributing to a presentation of total pain. 22 As benign DT and malignant sarcoma are both connective tissue diseases, they are seen at our institution within the same clinic and are treated by the same physicians and multidisciplinary approach. Thus, we formally investigated symptom distress in our patients with DT.…”
Section: Introductionmentioning
confidence: 99%
“…We evaluate DART scores in patient cohorts over time to identify predictors of distress for patients living with DT, and compare cross sectional DART scores between DT and sarcoma patients. 22 DART also includes the Informational Problems (understanding the illness, communication with the health care team, making treatment decisions, knowing about available resources) and Spiritual Problems (meaning/purpose in life, faith), domains from the Canadian Problem Checklist (CPC). 26 If a patient in either DT or sarcoma cohorts had completed more than one DART survey within the study time points, their most symptomatic DART score (highest distress) was used as our objective was to measure the highest distress levels patients experience during the management and surveillance of DT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although high intensity scores on distress screening tools may indicate a need for a specialized referral, other specialized areas, such as psychosocial oncology, have shown that many of the trigger criteria can be managed with more frequent assessment in the primary clinic first, and that patients can be referred out only when necessary. 9 Feldstain et al found that low-intensity symptom scores increased at the next follow-up appointment. This finding has been previously published, and various reasons have been hypothesized, including the volatility of symptoms and the relation to underlying disease progression.…”
mentioning
confidence: 99%